High-pressure torsion driven mechanical alloying of CoCrFeMnNi high entropy alloy. (1st January 2019) - Kilmametov, A.; Kulagin, R.; Mazilkin, A.; Seils, S.; Boll, T.; Heilmaier, M.; Hahn, H.
Abstract: Fully-dense bulk CoCrFeMnNi high entropy alloy (HEA) has been obtained by high-pressure torsion (HPT) deformation. Elemental, micrometer sized powders were successively mixed in equimolar proportions, consolidated and deformed at 5 GPa using imposed shear strain equivalent up to 100 rotations. Transmission electron microscopy, X-ray diffraction and 3D atom probe tomography were performed to study the microstructure evolution resulting from HPT-induced mechanical alloying. Single-phase, nanocrystalline (grain size of 50 nm) alloy with smaller chromium oxide precipitates (of 7–10 nm) exhibited a hardness of 6700 MPa, which is the highest one reported for as-processed bulk CoCrFeMnNi alloys to our best knowledge. Graphical abstract: Unlabelled Image